The wage gap among male and female top managers - Mendes,Raquel Vale (2008)
This paper studies gender wage differentials among top managers in the Portuguese economy. The objective is to investigate whether men and women within the same occupational group, with relatively high levels of human capital, and who are evaluated basically on their performance, are treated unequally in relation to pay. The Oaxaca wage decomposition method is used, relying on micro data from the Quadros de Pessoal (QP). The main findings indicate that a substantial portion of the wage gap between male and female top managers is potentially due to wage discrimination.